Veränderung der subfovealen Choroiddicke nach Kataraktoperation dargestellt mittels Enhanced Depth Imaging optischer Kohärenztomografie = Change in subfoveal choroidal thickness following cataract surgery imaged with Enhanced Depth Imaging optical coherence tomography - Mackenbrock, Lars; Weindler, Jan N.; Łabuz, Grzegorz; Baur, Isabella; Auffarth, Gerd U.; Khoramnia, Ramin (Klinische Monatsblätter für Augenheilkunde, 2023)
BACKGROUND: Due to its invasive nature, cataract surgery can lead to inflammatory processes in the posterior segment, which can result in prolonged recovery times, reduced functional outcomes, and late-onset complications. The aim of the current study was to identify wherever phacoemulsification parameters play a role in choroidal thickness change following cataract surgery. METHODS: This prospective single-center study enrolled 31 patients (31 eyes) scheduled to undergo routine cataract surgery. Patients with previous ocular surgeries, pathologies or general disorders affecting vision were excluded. Patients were examined preoperatively, as well as 1, 4, and 12 weeks after surgery. Corrected distance visual acuity (CDVA), intraocular pressure (IOP) as well as cumulative dissipated energy (CDE), ultrasound time (UT), and fluids used during surgery were recorded. Subfoveal choroidal thickness was measured manually by two masked independent experts using enhanced depth imaging (EDI) optical coherence tomography (OCT). Furthermore, cataract density was automatically calculated using a custom MATLAB script and an anterior segment OCT. RESULTS: Subfoveal choroidal thickness increased significantly (p < 0.001, Student's paired sample t-test) and continuously during the 12-week-long follow-up period. Both the nuclear lens density and the improvement in CDVA correlated significantly with this increase (r = 0.413, p = 0.021 and r = 0.421, p = 0.018, respectively). Neither the CDE (r = 0.334, p = 0.071), the UT (r = 0.102, p = 0.629), the amount of fluid used (r = 0.237, p = 0.27) nor the decrease in IOP (r = - 0.197, p = 0.288) showed any significant correlation with the choroidal swelling. CONCLUSION: Cataract surgery leads to an increase in subfoveal choroidal thickness. While no statistically significant correlation to the phacoemulsification parameters could be established, this might be because of a selection bias due to the technological constraints of the OCT. Nevertheless, the choroid might play a central role in early- and late-onset complications.